(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2014)
Stature is important parameter of personal identification of individual there are many studies conducted along with others parameters such as age, sex, race, etc. The present study is an attempt to examine the relationship between the stature and right middle finger length of 100 males of Karnataka, in South Indian Population in age ranging from 17 to 22 years. Linear and multiple regression equations formula for stature estimation were calculated. The co-relation co-efficient between stature and right middle finger length were found to be positive and statistically highly significant (P<0.01). The highest co-relation co-efficient is + 0.35. The regression formula was checked for their accuracy, applicability and reliability.